Mechanisms of management of Shipbuilding cluster systems - Zaporozhets, I. M.; Fateev, N. V.; Kozyr, B. Yu. (My University, 2018)
An effective tool for ensuring the competitiveness of shipbuilding enterprises is the application of a cluster approach. The shipbuilding cluster systems are functionally distributed logistics networks that evolve both nationally and internationally. The essence and features of the shipbuilding cluster systems in the work have been considered. The mechanisms of the organization of shipbuilding clusters are suggested as well as the indicators for evaluating the efficiency of their operation. The schemes of interaction of enterprises participating in the shipbuilding cluster have been developed. In this case, models and means of logistic management are used. For the logistics center, the functions of logistics support and the tasks of creating and maintaining a common information space of the cluster system are defined. The analysis of the system of planning and accounting units in shipbuilding is carried out, the scheme of decomposition for the organizational structure of the cluster is substantiated. It was proposed to use the corridor-scale network diagrams when planning work in a cluster. The scheme of interaction of the system of budgets and business processes at different levels of decomposition is substantiated.
Zaporozhets, I. M. Mechanisms of management of Shipbuilding cluster systems / I. M. Zaporozhets, N. V. Fateev, B. Yu. Kozyr // Innovative development of the economy: global trends and national features : collective monograph / edited by J. Žukovskis, K. Shaposhnykov. – Lithuania : Publishing House “Baltija Publishing”, 2018. – P. 563–574.
Keywords: logistics management; shipbuilding cluster system; logistics centers; process-oriented management; logistics networks; planning and accounting units in shipbuilding; organizational structure decomposition scheme